PROBLEMATIKA PENDIDIKAN SEKSUALITAS DALAM KURIKULUM PAI MODERN - Fakrur Razi (Yayasan An-Nur Meunara Baro, 2025)
This study investigates the challenges of integrating sexuality education into Indonesia’s Islamic Religious Education (PAI) curriculum at the secondary school level. Employing a qualitative approach with a multiple case study method, data were collected through content analysis of the 2013 curriculum documents and textbooks, as well as in-depth interviews with 15 PAI teachers and 10 contemporary Islamic legal scholars. The research identifies three major issues: (1) tension between religious norms and adolescents' reproductive health needs, (2) the gap between formal curriculum content and students’ social realities, and (3) cultural and psychological resistance to addressing sensitive topics in classroom settings. Notably, 78% of students reported that the current materials fail to address their real-life concerns. In response, this study proposes a contextual approach grounded in maqasid sharia, particularly the protection of life (hifz al-nafs) and dignity (hifz al-‘ird), alongside principles of adolescent developmental psychology. Recommended pedagogical strategies include value-based Islamic instruction, a family-based approach, and collaboration among educators, health professionals, and parents. Through these integrative and holistic strategies, sexuality education within the PAI framework can foster character development, critical understanding, and self-awareness among Muslim adolescents.